Optimalisasi Pendampingan Sertifikasi Halal Berbasis ESG dan Akuntansi Modern bagi UMKM - Raya Puspita Sari Hasibuan; Putri Syuhada; Nuraini Nuraini; Anriza Witi; Siti Asnida Nofianna (Forum Kerjasama Pendidikan Tinggi, 2026)
This Independent Community Service Program (PMKM) was conducted with Prahayuni MSME, a culinary business located in Medan Polonia District, Medan City, North Sumatra, Indonesia. Although the enterprise has considerable business potential, it faced several challenges that limited its competitiveness and business sustainability. The main problems included limited understanding of halal certification procedures and requirements, incomplete Halal Product Assurance System (HPAS) documentation, inadequate implementation of Environmental, Social, and Governance (ESG) principles in business operations, and a simple financial recording system that had not adopted modern accounting practices. This community service program aimed to strengthen the partner’s capacity to obtain halal certification through assistance in preparing HPAS documentation, implementing ESG principles, and improving financial management based on modern accounting to support sustainable business development. The program adopted a participatory empowerment approach consisting of needs assessment, socialization, technical training, assistance in preparing halal certification documents, guidance in using the SIHALAL application system, implementation of ESG-based business practices, training in simple financial reporting, and continuous monitoring and evaluation. The results demonstrated significant improvements in the partner’s knowledge and skills regarding halal certification requirements, the successful completion of HPAS documentation, improved financial recording practices that are more systematic and accountable, the initial implementation of ESG principles in business management, and the successful acquisition of a Halal Certificate for Prahayuni MSME products. These achievements contributed to strengthening business governance, increasing consumer confidence, expanding market opportunities, and providing an integrated community empowerment model that combines halal certification, ESG implementation, and modern accounting practices to enhance the competitiveness and long-term sustainability of MSMEs.